Causal relationships between immune cell traits and HER2 subtypes in breast cancer: a Mendelian randomization study - Fenfen Gu; Chuling Hu; Chao Li (Discover Oncology)
Abstract Background Breast cancer can be classified based on HER2 status into HER2-positive (HER2+) and HER2-negative (HER2-) subtypes, which differ significantly in pathogenesis, prognosis, and treatment response. Immune cells are critical components of the tumor microenvironment, influencing breast cancer progression. However, their specific roles in HER2 + and HER2- breast cancer subtypes are not yet fully understood. Methods This study applied Mendelian randomization (MR) analysis to investigate causal relationships between 731 immune cell phenotypes and breast cancer with different HER2 statuses. Genetic data were obtained from the Finngen and OPENGWAS databases. Inverse variance weighted (IVW) analysis and sensitivity tests were used to ensure the robustness of results. Results Our analysis revealed significant associations between specific immune cell traits and breast cancer subtypes. For instance, B cell traits such as “Sw mem %B cell” and “IgD- CD38- %B cell” were positively correlated with the development of HER2 + breast cancer. Conversely, traits associated with T cell maturation and myeloid cells demonstrated a negative correlation with HER2 + breast cancer. Regulatory T cell traits were more strongly linked to HER2- breast cancer. Conclusions Distinct immune cell profiles are associated with HER2 + and HER2- breast cancers. These findings provide insights into the immunological differences between subtypes and suggest potential targets for personalized immunotherapy strategies. Further research is required to clarify underlying mechanisms.